Synergistic Molecular Engineering of Hole‐Injecting Conducting Polymers Overcomes Luminescence Quenching in Perovskite Light‐Emitting Diodes. Issue 18 (16th June 2021) - Ahn, Soyeong; Kim, Young‐Hoon; Kim, Sungjin; Park, Jinwoo; Li, Nannan; Heo, Jung‐Min; Kim, Joo Sung; Kim, Dong Jin; Hong, Byung Hee; Lee, Jin Yong; Lee, Tae‐Woo
Abstract: Electroluminescence efficiency and operating stability of solution‐processed perovskite light‐emitting diodes (PeLEDs) are limited by luminescence quenching induced by indium or tin released from indium tin oxide (ITO) electrode upon deposition of highly acidic conventional hole injection layer (HIL) (i.e., poly(3, 4‐ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS)) and inefficient hole injection into perovskite emitting layer. Here, a synergistic molecular strategy to develop a neutralized gradient HIL, which possesses low acidity and high work function ( WF ) simultaneously, is proposed. First, it is shown that aniline with relatively low basicity and dipole moment efficiently neutralizes HIL while maintaining its original confirmation and high WF . Both acidity‐neutralizing aniline and WF ‐modifying agent (perfluorinated ionomer) are incorporated into PEDOT:PSS to achieve high pH ≈ 6 and WF  > 5.8 eV, which suppresses etching of underlying ITO and luminescence quenching while maintaining efficient hole injection into perovskite emitting layer. With this synergetic molecular engineering, high current efficiency = 52.55 cd A −1 with extended operating lifetime is achieved in PeLEDs that use colloidal formamidinium lead bromide nanoparticle films. This result provides a simple and efficient way to develop efficient and stable PeLEDs in industrial displays and solid‐state lighting. Abstract : Neutralized hole injection layer with high work function ( WF ) is realized by incorporating both acidity‐neutralizing additive (aniline) and WF ‐modifying agent (perfluorinated ionomer) into the poly(3, 4‐ethylenedioxythiophene):poly(styrene sulfonate). As a result, etching of underlying metal electrode and luminescence quenching are prevented and efficient hole injection and current efficiency of 52.55 cd A −1 with extended operating stability are achieved in perovskite light‐emitting diodes.